Effects of topical Polymyxin Neomycin Hydrocortison in Patients with Non-Allergic Rhinitis, a randomized clinical trial. - Majid Mirsadraee; Sara Mollazadeh; Negin Ghiyasimoghaddam (Journal of Medical Bacteriology)
Background and aims: Bacterial infection is involved in the pathogenesis of inflammatory non-allergic rhinitis (NAR), and a broad-spectrum antibiotic should reduce the severity of the disease by eliminating the mucosal biofilm. The purpose of this study is to assess the efficacy of a topical mixture of polymyxin, neomycin, and hydrocortisone in patients with NAR Materials and Methods: This double-blind phase 3 randomized clinical trial was conducted on 90 patients with non-allergic rhinitis (NAR) in Mashhad, Iran. The subjects experienced symptoms for more than two weeks, and the pretrial course of topical corticosteroids was ineffective. Patients were randomly assigned to treatment groups receiving polymyxin NH, hydrocortisone, or saline. The drug was administered as nasal drops three times daily for a treatment course of two weeks, and the containers were identical. The primary outcome was nasal obstruction. Results: The pretrial comparison showed no significant difference between groups in terms of clinical findings. However, after the trial, nasal obstruction, as the primary outcome, significantly decreased from 20 subjects (66%) to 7 subjects (23%) in the Polymyxin NH group, along with other secondary outcomes, including palatal itching (56% to 23%), sneezing (76% to 40%), mucosal inflammation (100% to 75%), post-nasal drip (PND) (96% to 63%), and concha swelling (96% to 73%). In the other groups, sneezing was the only significant improvement observed in the saline group. Cytology of nasal discharge showed a reduction in nasal neutrophil counts in the Polymyxin NH group (68±16.7% to 46±27.6%) compared to the hydrocortisone and saline-treated groups. Conclusions: Topical intranasal polymyxin NH is effective in treating patients with non-allergic rhinitis.